1984
DOI: 10.1099/00221287-130-1-45
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Ferric Iron by Heterotrophic Bacteria in Lake Sediments

Abstract: The addition of Fe(II1) to anoxic lake sediments decreased the quantity of volatile fatty acids which accumulated. Similarly, the addition of several substrates to the sediments stimulated the rate of reduction of the naturally occurring Fe(II1). Of the substrates used, malate caused the greatest stimulation, and subsequently a malate-fermenting Vibrio was isolated from the sediment. This organism also reduced NO, and Mn(IV), the addition of which to the growth medium significantly lowered the rate of Fe(1I) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

1989
1989
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 18 publications
2
50
1
Order By: Relevance
“…nov. NRB also perform iron reduction (Sørensen, 1982 ;Jones et al, 1983Jones et al, , 1984Lovley & Phillips, 1988), we wanted to test strain N2460 T for this trait. As mentioned, however, ferric pyrophosphate reacted chemically with sulfide in the medium, raising the redox potential and causing growth inhibition of the bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…nov. NRB also perform iron reduction (Sørensen, 1982 ;Jones et al, 1983Jones et al, , 1984Lovley & Phillips, 1988), we wanted to test strain N2460 T for this trait. As mentioned, however, ferric pyrophosphate reacted chemically with sulfide in the medium, raising the redox potential and causing growth inhibition of the bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…transferred only 0.13 or 0.03% of the reducing equivalents available in glucose or malate to Fe(III) (159). Malate fermentation resulted primarily in the accumulation of organic acids and ethanol.…”
Section: Fermentative Fe(hii) and Mn(iv) Reducersmentioning
confidence: 99%
“…Starkey and Halverson (289) found that Fe(III) was reduced in anaerobic cultures of Clostridium sporogenes or E. coli growing in a glucose or peptone medium, and Roberts (272) found that Bacillus polymyxa reduced Fe(III) while fermenting glucose. Subsequent studies found that a wide variety of fermentative microorganisms reduced Fe(III) or Mn(IV) during anaerobic growth (45,46,128,158,159,226,245,246), and organisms capable of reducing Fe(III) and Mn(IV) under aerobic culture conditions have also been described (76,82,86,316).…”
Section: Fermentative Fe(hii) and Mn(iv) Reducersmentioning
confidence: 99%
See 1 more Smart Citation
“…Ottow3) re ported that iron reducers belownged to family Enterobacteriaceae, Bacillaceae, methanogenic clostridia, or sulfate reducing bacteria. Jones et al 5,6) found a strain of Vibrio has high activity in producting acetic acid and in reducing iron. In this study, the dominant genera of iron-sol ubilizing bacteria were Bacillus, Lactobacillus, and …”
Section: Production Of Organic Acids and The Dissolution Of Ironmentioning
confidence: 99%